Trends, Atmospheric Patterns, and Spatial Variability of Heatwaves in an Oceanic Climate Area of NW Iberia - Luis Pérez-García; Cristina García-Hernández; Jesús Ruiz-Fernández (Land)
In the Atlantic region of northern Spain, heat extremes were historically rare, but in recent decades, they have become more intense and persistent. This article characterizes heat events in Asturias (NW Spain) between 2001 and 2023, focusing on their frequency, intensity, and duration, as well as their temporal trends. Additionally, it explores the synoptic patterns linked to these episodes to enhance understanding of their occurrence and evolution over the study period. The research is based on official meteorological records, and it distinguishes between officially declared heatwaves (DHs) and significant heat events (SHEs) identified through regional press reports. This methodology enables the study to capture a broader spectrum of heat-related impacts. During the study period, 17 episodes were documented (11 DHs and 6 SHEs). The frequency, intensity, and duration of heat events have significantly increased, particularly since 2016, standing the last two years (2022 and 2023). Both DHs and SHEs have progressively shifted toward the early and late periods of the astronomical summer, with some events occurring during spring and autumn in the second half of the study period (years 2017, 2022, and 2023). Three atmospheric patterns have been identified as responsible for extreme heat episodes; Type 1 (warm tropical continental air masses, combined with atmospheric stability) is responsible for 10 of the episodes. Furthermore, urban areas and main river valleys were the most affected areas, while coastal regions remained largely unaffected. This research aims to contribute to a broader understanding of how heatwaves are evolving in a temperate climate area under the influence of global warming, providing insights to inform and improve adaptation strategies for mitigating their impacts.